Pengaruh Keadilan Organisasi Terhadap Komitmen Organisasi Pegawai Pada Jurusan Administrasi Niaga Politeknik Negeri Ambon - Joseph Marvelous Wattimena; Elsina Huberta Aponno; Join Rachle Luturmas (P3M Politeknik Negeri Ambon, 2024)
The initial survey at the Ambon State Polytechnic Department of Business Administration showed that there were indications of problems with organizational justice and organizational commitment to employees. This study aims to determine whether organizational justice affects the organizational commitment of employees at the Department of Commercial Administration, State Polytechnic of Ambon. The analytical method used in this research is descriptive analysis and simple linear regression analysis. Descriptive analysis shows that organizational justice in the Department of Business Administration Ambon State Polytechnic has an average value of 3.39 which is interpreted as quite good, while employee organizational commitment has an average value of 3.45 which is interpreted as good. The results of the regression analysis show that organizational justice has a positive and significant effect on employee organizational commitment at the Department of Business Administration, State Polytechnic of Ambon. Based on these results, it can be concluded that the better the organizational justice, the better the employee's organizational commitment. To improve it, the Ambon State Polytechnic Business Administration Department must strive to improve organizational justice by paying attention to distributive justice, procedural justice, and interactional justice. Employee organizational commitment can be maintained and even increased by paying attention to indicators of identification, loyalty and involvement. Keywords: Organizational Justice, Organizational Commitment.